Effect of copper-Titanium bimetallic nanoparticles embedment in the structural and optical properties of tellurite glass - Khasidah Kamarudin (2020)
The combination of bimetallic nanoparticles (NPs) in tellurite glass becomes an emerging issue due to the beneficial features offered scientifically and technologically. The embedment of copper and titanium NPs in the glass matrix is the focus of this research. Two series of glass with general composition of (70 - Xy) Te0»- 20Zn0 - 9Naz0 - 1ErOs = (x)CuO - (y)TiO; where x= 0.0, 0.04 and 0.1 mol%; y = 0.0, 0.04 and 0.1 mol% are prepared via melt-quenching technique. XRD spectra verify the amorphous nature of all glass samples with a presence of a broad hump around 25° - 40°. SEM images give information on the surface morphology and EDX spectra illustrates the elemental traces of Te, Er, Na, Zn, C, 0, Cu, Ti, and Au. The aspect ratio from the TEM images of TZNECu0.1, TZNETi0.1, and TZNECu0.1Ti0.1 glass sample displays the non-spherical shape of NPs in the range of 1-3, 1.00- 2.66 and 1.1-2.7, respectively. Meanwhile, the TZNECu0.1Ti0.04 glass sample shows the formation of core-shell NPs in which the inner and outer diameter lies in the range of 36.05 nm and 4.25 nm, respectively. FTIR spectra show the Cu-0, Zn- 0, Te-O, Te0», Te0», and Cu- H bonds. The absorption band for all glass samples consists of seven peaks originates from the transition of Er? ions from the ground state of Isn to the Fsz, Fn, Hit/, Ssp, Fan, Is/z, and I/a excited states. The variation in the direct bandgap, indirect bandgap and Urbach energy for all glass samples is due to the contribution of bimetallic Cu/Ti NPs. The SPR plasmon bands for the first series and the second series of glass are lies in the range of 671- 816 nm and 670- 809 nm. The upconversion emission of Er? ions shows the green emission centred at 545 nm represent the 'Ssn> Isa transitions. The enhancement in the PL intensity for the glass in the first series and second series with a factor of 0.20 - 1.07 and 0.20 - 2.59 is due to the contribution of bimetallic NPs. The enhancement in the SPR band and photoluminescence make the glass is suitable for photonic device application.